Gamelan Sebagai Simbol Estetis Kebudayaan Masyarakat Jawa - Hananto, Fariz (representamen, 2020)
Supporting music has the power to represent the culture of a person or group at a particular time. He understood to have a basis for understanding, determining the ways and actions in each note produced. The color of the voice, the pitch and the musical work in each region have many differences. Because in essence, music is a work of art that is here is an aesthetic symbol of every different cultural community.Gamelan is a musical instrument that represents or depicts Javanese culture. Some Javanese gamelan in Surakarta, Yogyakarta and Cirebon, among others are Kyai Guntur Madu, Kyai Guntur Sari, Kyai Naga Wilaga and Gong Sekati. That every gamelan has aesthetic symbols that are attached and contained in the laras, embat, gending, deferment, wasps and repeto technique. These 6 factors reflect Javanese culture such as beliefs, language, philosophy, livelihoods and social relations which are still faced and preserved. Research symbols are concentrated in each gamelan, intrinsic, extrinsic and instrumental symbols. The three are interrelated and elaborated on the message or meal that is presented about Javanese culture.Keywords: Gamelan, Aesthetic Symbols, Javanese Culture